Znaczenie Metody Krakowskiej w procesie wspomagania rozwoju dzieci z uszkodzonym słuchem - Jakoniuk-Diallo , Anna; Wojciechowska, Adrianna (Studia Edukacyjne, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*70.87px); top: calc(var(--scale-factor)*388.37px); font-size: calc(var(--scale-factor)*8.00px); font-family: serif; transform: scaleX(1.13825);" role="presentation">The variety of therapeutic tools available in the rehab process of children with disabilities is being <span dir="ltr" style="left: calc(var(--scale-factor)*70.87px); top: calc(var(--scale-factor)*398.37px); font-size: calc(var(--scale-factor)*8.00px); font-family: serif; transform: scaleX(1.11139);" role="presentation">extended. Many procedures created in the second half of the 20<span dir="ltr" style="left: calc(var(--scale-factor)*296.20px); top: calc(var(--scale-factor)*398.20px); font-size: calc(var(--scale-factor)*4.66px); font-family: serif; transform: scaleX(1.16664);" role="presentation">th <span dir="ltr" style="left: calc(var(--scale-factor)*302.61px); top: calc(var(--scale-factor)*398.37px); font-size: calc(var(--scale-factor)*8.00px); font-family: serif; transform: scaleX(1.11592);" role="presentation">century is still used nowadays. The <span dir="ltr" style="left: calc(var(--scale-factor)*70.87px); top: calc(var(--scale-factor)*408.37px); font-size: calc(var(--scale-factor)*8.00px); font-family: serif; transform: scaleX(1.10242);" role="presentation">range of their users is permanently increasing, which results in adding new methodological modifica<span dir="ltr" style="left: calc(var(--scale-factor)*70.87px); top: calc(var(--scale-factor)*418.37px); font-size: calc(var(--scale-factor)*8.00px); font-family: serif; transform: scaleX(1.11523);" role="presentation">tions. The Krakow Method is not an exception, as it was originally created for children with hearing <span dir="ltr" style="left: calc(var(--scale-factor)*70.87px); top: calc(var(--scale-factor)*428.37px); font-size: calc(var(--scale-factor)*8.00px); font-family: serif; transform: scaleX(1.12001);" role="presentation">difficulties. Currently, it is also used to treat people affected by genetic disorders which requires de-<span dir="ltr" style="left: calc(var(--scale-factor)*70.87px); top: calc(var(--scale-factor)*438.37px); font-size: calc(var(--scale-factor)*8.00px); font-family: serif; transform: scaleX(1.0986);" role="presentation">veloping new strategies adapted to such patients. The text aims at evaluating selected strategies of the <span dir="ltr" style="left: calc(var(--scale-factor)*70.87px); top: calc(var(--scale-factor)*448.37px); font-size: calc(var(--scale-factor)*8.00px); font-family: serif; transform: scaleX(1.103);" role="presentation">Krakow Method in the context of early development of children with hearing difficulties.